2022
DOI: 10.3390/ijms232113143
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ovulation-Related Gene Expression during Induced Ovulation in the Amur Sturgeon (Acipenser schrenckii) Ovarian Follicles

Abstract: The luteinizing hormone (LH) and maturation-inducing steroids (MIS), such as 17α,20β-dihydroxy-4-pregnen-3-one, regulate the final oocyte maturation in teleosts. Oocyte maturational competence (OMC) and ovulatory competence measure the sensitivity to MIS for oocyte maturation and ovulation, respectively. However, the molecular mechanisms underlying the acquisition of ovulatory competence remain unknown. Sturgeons are an excellent research model for investigating these mechanisms. We examined the seasonal profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In addition to structural proteins, other ECM components, such as cathepsins (pro-cathepsin H (CTSH), dipeptidyl peptidase 1 (CTSC), and cathepsin D (CTSD)), PLG, matrix metalloproteinase-2 and 9 (MMP2, MMP9), and their metalloproteinase inhibitor 4 (TIMP4), are involved in follicular remodeling and the breakdown of the follicle wall during ovulation [ 41 43 ]. Recent studies also suggested the involvement of the plat/plasmin system in ECM remodeling during ovulation in sturgeon [ 44 ], which further supports the dynamic nature of the ECM in the sturgeon ovary. ECM proteins, such as myocilin (MYOC), thrombospondin-4 (THBS4), cadherin 13 (CDH13), leucine-rich repeat-containing protein 15 (LRRC15), and tetranectin (CLEC3B), may contribute to cell adhesion and signaling within the ovary in sturgeon.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to structural proteins, other ECM components, such as cathepsins (pro-cathepsin H (CTSH), dipeptidyl peptidase 1 (CTSC), and cathepsin D (CTSD)), PLG, matrix metalloproteinase-2 and 9 (MMP2, MMP9), and their metalloproteinase inhibitor 4 (TIMP4), are involved in follicular remodeling and the breakdown of the follicle wall during ovulation [ 41 43 ]. Recent studies also suggested the involvement of the plat/plasmin system in ECM remodeling during ovulation in sturgeon [ 44 ], which further supports the dynamic nature of the ECM in the sturgeon ovary. ECM proteins, such as myocilin (MYOC), thrombospondin-4 (THBS4), cadherin 13 (CDH13), leucine-rich repeat-containing protein 15 (LRRC15), and tetranectin (CLEC3B), may contribute to cell adhesion and signaling within the ovary in sturgeon.…”
Section: Discussionmentioning
confidence: 63%